'Ethnic' media and election campaigns: Chinese and Indian media in New Zealand's 2017 election. Issue 2 (3rd April 2021) - McMillan, Kate; Barker, Fiona
ABSTRACT: This article provides the first systematic study of the political content of New Zealand's Chinese and Indian print and online news media during an election campaign period. We assess the comprehensiveness and political balance of election coverage provided by a sample of high-circulation New Zealand-based Chinese and Indian news publications during New Zealand's 2017 campaign. Overall, we find all the publications in our sample under-reported minor parties and, in some cases, the quantity and tone of their reporting demonstrated strong bias towards the National Party. These findings are significant in a context where such media play an important role in informing ethnic and immigrant minorities during campaigns, and where such minorities form a growing proportion of the New Zealand electorate.